Development of Learning Devices Based on Realistic Mathematical Learning Models to Improve Mathematical Literary Ability - Nazri Maulana Khani Selian; Mulyono Mulyono; Mariani Mariani (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
The limited usage and repurposing of media in education served as the driving force behind this study. Student Textbooks and Student Worksheets (LKPD) are designed to support instruction. Additionally, Systems of Two Variable Linear Equations (SPLDV) implicit graphical problem solutions are made possible with the use of GeoGebra media. In this inquiry, interactive learning tools for the SPLDV curriculum will be made using GeoGebra. The 4-D Thiagaradjan model serves as a model in this study on development. Define, design, develop, and deploy are the four stages. This experiment involved eighth-graders aged 14 and two eighth-grade math teachers. Utilizing a requirements analysis, interviews, and questionnaires, observational data was gathered. An study of the data collection process's demands, as well as interviews and surveys, are all included. Validity, practicability, and efficacy were three essential development conditions that had to be met before a study could be put into action. Proportion scores were validated by two qualified validators to support the study's conclusions. For learning device formats, graphics, language, and content validation, the average score is 3.78. (Applicable classifications). The effective category, which received an average score of 74.3 on the pretest and 87 on the posttest, the complete category, which served as a gauge of the teacher's capacity to manage learning and received an average score of 4.4 in the very good category, and the practical category, which also received an average score of 4.4 in the very good category, served as the foundation for the research findings. As a result, improving student performance can be accomplished through the development of learning tools based on realistic learning models.Keywords: Development of Learning Devices, Thiagaradjan 4-D Model, Realistic Mathematical Education (RME), Mathematical Literacy.